1989
DOI: 10.1111/j.2044-8279.1989.tb03108.x
|View full text |Cite
|
Sign up to set email alerts
|

Pupils‘ Perceptions of School and Teachers Ii ‐ Relationships With Motivation and Approaches to Learning

Abstract: The previous article has described the development of scales designed to measure pupils' perceptions of school and teachers. Previous comparative studies have shown interesting differences in motivation and approaches to learning between Britain and Hungary, which were considered to reflect different methods of teaching. This article explores the relationships between a set of inventory scores describing perceptions of school and teachers and another set indicating school motivation and approaches to learning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Their study has shown positive association between a scale representing good teaching (well prepared, helpful, committed teachers) with a scale representing meaning orientation to studying (deep approach, inter-relating ideas, use of evidence and intrinsic motivation). In a study conducted by Entwistle, Kozeki and Tait (1989), scale scores describing perceptions of school and teachers have shown positive relationships with level of motivation and approaches to learning. Pimparyon et al (2000) observed significant positive relationships between meaning orientation and all the five scales of the medical education environment measure: students' perception of teaching and learning, teachers, academic atmosphere, self and social perceptions.…”
Section: Introductionmentioning
confidence: 95%
“…Their study has shown positive association between a scale representing good teaching (well prepared, helpful, committed teachers) with a scale representing meaning orientation to studying (deep approach, inter-relating ideas, use of evidence and intrinsic motivation). In a study conducted by Entwistle, Kozeki and Tait (1989), scale scores describing perceptions of school and teachers have shown positive relationships with level of motivation and approaches to learning. Pimparyon et al (2000) observed significant positive relationships between meaning orientation and all the five scales of the medical education environment measure: students' perception of teaching and learning, teachers, academic atmosphere, self and social perceptions.…”
Section: Introductionmentioning
confidence: 95%
“…However, teachers often are seen as less important than parents are in impacting children's lives (Furman & Buhrmester, 1992). Comparing students' perceptions of parents' and teachers' support for their academic endeavors would shed light on the relative importance of students' relationships for their academic success (Paulson, Marchant, & Rothlisberg, 1998).Furthermore, the general school climate characterized by a sense of competence, community, and positive expectation is known to be related to students' academic well being (Entwisle, Kozeki, & Tait, 1989;Epstein & McPartland, 1976;Rutter, Maughan, Mortimore, & Ouston, 1979). Students' perceptions of an overall school environment that is safe and supportive is critical to their school success.…”
mentioning
confidence: 97%
“…This finding suggests an intriguing avenue for future research. Some theorists have persuasively argued that pupils continually evaluate schools and teachers, they feel committed to schooling when teachers are perceived as honouring their 'contractual commitments', but will develop negative attitudes to learning when teachers are perceived as failing to meet these commitments (Elkind, 1971;Nisan, 1989; see also Entwistle, Kozeki & Tait, 1989b). Pupils' expectations of teachers probably reflect their perceptions of teachers' contractual commitments.…”
Section: Discussionmentioning
confidence: 99%